Peroxide assisted adsorption for treating palm oil mill effluent using palm shell based activated carbon / Kwong Chia Jun - Kwong, Chia Jun (2021)
In Malaysia, palm oil production is one of the major agricultural industries, attributing 37.9 % of the agricultural contribution to Gross domestic product (GDP). Among them, POME is the largest wastes generated from the palm oil mills production with high BOD, COD, TS, TSS, colour more than 500 ADMI. Since POME is considered as highly recalcitrant, the Department of Environment is started to be more stringent in standard discharge limits to control water pollution. Therefore, this study aimed to develop green hybrid adsorbent from activated PKS by integrating iron oxide and zeolite to treat POME. Palm kernel shell-based activated carbon (PKSAC) was incorporated with zeolite and iron oxide (Fe) to synthesize Zeolite-Fe/PKSAC and Fe/PKSAC adsorbents. The adsorbents have been prepared using co-precipitation and ultrasonic-assisted mixing processes and analyzed for surface functional group, morphology, N2 adsorption porosity, magnetic properties, and stability. The result showed that Zeolite-Fe/PKSAC and Fe/PKSAC have predominant mesoporous structures with a high surface area up to 619 m2/g for Fe/PKSAC and 573 m2/g for Zeolite-Fe/PKSAC. Both adsorbents also illustrated a high magnetic saturation of 16.6 emu/g and 10.6 emu/g for Fe/PKSAC and Zeolite-Fe/PKSAC, respectively. The adsorption efficiency of both adsorbents was investigated with and without the addition of H2O2 for POME removal. The effects of operating parameters that include H2O2 dosage, adsorbent dosage, contact time and initial pH of solution on the adsorption process, were investigated. The adsorption study using Fe/PKSAC without H2O2 showed that Fe/PKSAC had higher colour removal (93 %) than Zeolite-Fe/PKSAC (88 %) 5 g/L of adsorbent was used at pH 3 for 40 min of contact time. However, Zeolite-Fe/PKSAC revealed a higher chemical oxygen demand removal of 63 % compared to Fe/PKSAC (58 %). The reusability analysis also indicated that Zeolite-Fe/PKSAC has higher stability as it maintains its adsorbent capacity over five cycles, with just a decrease of 6 % compared to Fe/PKSAC. The adsorption of POME using Zeolite-Fe/PKSAC and H2O2 had successfully removed 83 % colour and 67 % COD using a lesser amount of adsorbent of 4 g/L and H2O2 of 68 mM, within a shorter reaction time of 30 minutes compared to Fe/PKSAC. Besides, Zeolite-Fe/PKSAC+H2O2 found to maintain its adsorbent potential up to the 5th cycle with a reduction of just 3 % of adsorption efficiency compared to Fe/PKSAC+ H2O2 (7 %). Zeolite-Fe/PKSAC+H2O2 also achieved the highest adsorption capacity of 73 mg/g as compared to Fe/PKSAC+H2O2 (55 mg/g), Zeolite-Fe/PKSAC (48 mg/g) and Fe/PKSAC (44 mg/g). In conclusion, the study has proven that the incorporation of iron oxide and zeolite into palm kernel shell activated carbon enhances the stability, separability and surface area of the adsorbents. The peroxide-assisted adsorption process using Zeolite-Fe/PKSAC greatly improved the reusability and adsorption efficiency of the adsorbent, minimizing the dosage of the adsorbent while reducing contact time.